Occupational Stress among Health Nurses Working in Health Services Centers in Gonbad Kavous - 2016 - Alireza DEHDASHTI; Meysam KARAMI; Bibi Sara SAMARI; Mahshid BAHRAMI; Ahmad JAHED (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: Occupational consequences and their effects on health and healthcare workers have been examined in many studies. Occupational stress is recognized as an important risk factor in the creation of physical and chronic mental disorders and the quality of work performance. Therefore, this study was carried out with the aim of investigating the stress induced by the work and some social factors among the Health Nurses Working in town Gonbad Kavous in 2016. Methods: This cross-sectional descriptive-analytic study was performed on 147 health workers in Gonbad Kavous town. in order to collect data, the HSE questionnaire including 35 questions with seven fields, role, communication, support of  Authorities,  Fellow support, control, demand and change were used. data analyzed and evaluated by SPSS22 software Results: The mean and standard deviation Health Nurses of age were 43.29 ± 6.50 years. Approximately 40% of health nurses experienced as Intense up to very intense occupational stress. Also, there was a significant relationship between age group (P=0.023), gender (P=0.015), education level (P=0.043), number of children (P=0.046) and financial status (P=0.028) with job stress level of health care workers. Conclusion: The results indicate a high prevalence of occupational stress among health nurses. It seems that assessing work-related stresses of health nurses can lead to appropriate identification of occupational injury risk factors. Also, interventional studies are needed to Compilation a stress management program for health nurses and in order to Coping with work-related stress.